That's not my polar bear-- - Watt, Fiona; Wells, Rachel (London, England Usborne Publishing, 2009)
A little mouse searches for its polar bear, using textures to help identify the right one
English Stories
1
Keywords: Polar bear -- Juvenile fiction; Mice -- Juvenile fiction